Some Fixed Point Theorem for Mapping on Complete G-Metric Spaces - Fadi Awawdeh; Hamed Obiedat; Zead Mustafa (Fixed Point Theory and Applications, 2008)
We prove some fixed point results for mapping satisfying sufficient conditions on complete G-metric space, also we showed that if the G-metric space (X,G) is symmetric, then the existence and uniqueness of these fixed point results follow from well-known theorems in usual metric space (X,dG), where (X,dG) is the usual metric space which defined from the G-metric space (X,G).